Health surveillance: proposal for a tool to evaluate technological arrangements in local health systems Vigilância em saúde: proposta de ferramenta para avaliar arranjos tecnológicos em sistemas locais de saúde - Gerluce Alves Pontes da Silva; Ligia Maria Vieira- (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
In order to identify the various meanings ascribed to health surveillance, the authors conducted a systematic review of articles published from January 1990 to August 2005 in the following databases: LILACS, SciELO, CAPES, MEDLINE, and Web of Science. A total of 144 abstracts were read and 18 full texts of Brazilian articles were selected for in-depth analysis, leading to the design of a typology for technological arrangements related to the various meanings: (i) traditional epidemiological surveillance, with communicable diseases as the main object; (ii) public health surveillance, as the municipal component of the national health surveillance system; and (iii) health surveillance, a technological mode of organizing health practices in a given territory. The proposed typology can contribute to research on surveillance practices in local health systems. It can also serve as a template for data collection and analysis. The meanings ascribed to the three types are discussed in light of public health's historical development as a field. Com o objetivo de identificar os significados dos diversos termos empregados acerca da vigilância em saúde, realizou-se uma revisão sistemática da bibliografia especializada sobre o tema, no período compreendido entre janeiro de 1990 a agosto de 2005, nas bases de dados do LILACS, SciELO, banco de teses da CAPES, MEDLINE e Web of Science. A análise de 144 resumos e de 18 textos exemplares selecionados na literatura nacional permitiu a elaboração de uma matriz com a caracterização de três tipos ideais de arranjos tecnológicos possíveis em sistemas municipais de saúde: (i) vigilância epidemiológica tradicional, com as doenças transmissíveis como objeto; (ii) vigilância em saúde pblica, componente municipal do sistema nacional de vigilância em saúde; e (iii) vigilância da saúde, um modo tecnológico de organização das práticas de saúde em um dado território. A matriz proposta poderá contribuir para a realização de investigações sobre a implantação de práticas de vigilância em sistemas locais de saúde, norteando a coleta e análise dos dados. São discutidos os significados dos três tipos encontrados frente à constituição histórica do campo da saúde coletiva e da vigilância em particular.